PENGELOLAAN SAMPAH BERBASIS ZERO WASTE DI LINGKUP MAHASISWA JURUSAN ANTROPOLOGI FAKULTAS ILMU BUDAYA UNIVERSITAS HALU OLEO - La Janu; Wa Ode Winesty Sofyani; Baskara, Benny (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
This activity aims to transfer knowledge on zero-waste-based waste management, emphasizing the 5R principles (Reduce, Reuse, Recycle, Replace, and Replant). The concept encourages that waste, often deemed useless, does not always have to end up in final disposal sites. The activity is designed to motivate students from the Department of Anthropology, Faculty of Cultural Sciences, Halu Oleo University, to take responsibility for the waste they produce daily. Students living in on-campus boarding houses, if lacking concern and shared responsibility for managing waste in their environment, risk creating unsanitary and unhealthy living conditions. The implementation of this activity utilizes two techniques: counseling and training. Counseling is conducted through lectures, followed by a question-and-answer session between the presenter and participants. Training involves practical activities, starting with demonstrations by the facilitator, and followed by individual and group practice by the participants. The results of this activity show that students were motivated to begin implementing their own waste management and utilization strategies. They were encouraged to create items from waste materials that remain useful and practical. Through this activity, anthropology students gained new knowledge on how to manage organic and inorganic waste wisely. This process enables them to transform waste into items with functional, artistic, and economic value. --- Kegiatan pengabdian ini merupakan upaya transfer pengetahuan pengelolaan sampah berbasis zero waste yang menekankan prinsip 5R (Reduce, Reuse, dan Recycle, Replace dan Replant), dengan demikian sampah yang selama ini dianggap tak berguna tidak harus selalu berakhir di Tempat Pembuangan Akhir (TPA). Kegiatan ini bertujuan memotivasi mahasiswa Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo untuk bertanggungjawab atas sampah masing-masing yang dihasilkan sehari-hari. Mahasiswa yang tinggal di kos-kosan lingkungan kampus, bila tidak ada kepedulian dan tanggungjawab bersama terhadap sampah di lingkungannya maka berpotensi menghadirkan suasana kumuh dan tidak sehat. Pengabdian ini terdiri dari dua kegiatan, yakni penyuluhan dan pelatihan. Kegiatan penyuluhan dilakukan dengan metode ceramah, dilanjutkan dengan tanya jawab antara pemateri dan peserta. Kegiatan pelatihan dilakukan dengan metode praktik, terlebih dahulu memberi contoh, selanjutnya peserta mempraktikan secara perorangan dan kelompok. Hasil dari pengabdian ini telah memotivasi mahasiswa untuk mulai menerapkan pengelolaan dan pemanfaatan sampah masing-masing, sehingga dapat menghasilkan sesuatu yang bermanfaat. Melalui kegiatan ini, mahasiswa Antropologi dapat memperoleh pengetahuan baru bagaimana mengelola sampah organik dan anorganik dengan bijak, serta dapat menjadi sesuatu yang dapat memiliki nilai fungsi, nilai seni, dan nilai ekonomi.